1997
DOI: 10.1080/009841097159980
|View full text |Cite
|
Sign up to set email alerts
|

Ozone-Induced Dna Strand Breaks in Guinea Pig Tracheobronchial Epithelial Cells

Abstract: Ozone (O,), the major oxidant of photochemical smog, is thought to be genotoxic and a potential respiratory carcinogen or promoter of carcinogenic processes. Because of oxidative reactions with the mucus in the upper airway, 0, reaction products are able to penetrate into the tracheobronchial epithelial (TE) cells. The carcinogenic effects of 0, on the TE cells are especially of interest since most previous studies have focused on the morphology or permeability changes of tracheas only. Therefore, the objectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

1999
1999
2010
2010

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 27 publications
1
5
0
Order By: Relevance
“…More recently it has been shown that ozone is capable of inducing DNA strand breaks upon in vitro exposure of cells of the respiratory tract [Lee et al, 1996;Ferng et al, 1997] and human leukocytes, via hydrogen peroxide formation [Diaz-Llera et al, 2002]. This paper is the first report of an association between ozone concentration in urban air and DNA damage in the nasal mucosa of humans.…”
Section: Discussionmentioning
confidence: 91%
“…More recently it has been shown that ozone is capable of inducing DNA strand breaks upon in vitro exposure of cells of the respiratory tract [Lee et al, 1996;Ferng et al, 1997] and human leukocytes, via hydrogen peroxide formation [Diaz-Llera et al, 2002]. This paper is the first report of an association between ozone concentration in urban air and DNA damage in the nasal mucosa of humans.…”
Section: Discussionmentioning
confidence: 91%
“…DNA damage stimulates polyADP-ribosylatio n as an apparent requirement for DNA repair (Shall, 1984(Shall, , 1994Satoh & Lindahl, 1992;Malanga & Althaus, 1994), since the inhibitor of polyADPR synthetase greatly retards the DNA repair process (Cristóvâo & Rueff, 1996;Ménissier de Murcia et al, 1997;Trucco et al, 1998;Masutani et al, 1999). As mentioned in the introduction, a number of authors (Hamelin et al, 1978;Van der Zee et al, 1987a, 1987bRithidech et al, 1990;Görsdorf et al, 1990;Lee et al, 1995Lee et al, , 1996Ferng et al, 1997;Haney & Connor, 1999) have demonstrated that O 3 and NO 2 can cause DNA damage both in vitro and in vivo. In a previous publication (Bermúdez et al, 1999), we also demonstrated that ozone and nitrogen dioxide can cause DNA strand breaks in alveolar macrophages of rats exposed to similar conditions used in the present study.…”
Section: Discussionmentioning
confidence: 90%
“…Experiments (Rithidech et al, 1990) have demonstrated that in vivo exposure to ozone can cause chromosome damage in rat alveolar macrophages. More recently, other research groups have demonstrated that ozone can cause DNA strand breaks after in vivo exposure of rat tracheobronchial epithelial cells (Ferng et al, 1997), rat alveolar macrophages (Bermúdez et al, 1999), and mouse lung cells (Haney & Connor, 1999). As mentioned earlier, the ability of NO 2 and O 3 to generate free radicals suggests that damage to DNA and the subsequent DNA repair response may represent an important component of their toxicity.…”
mentioning
confidence: 98%
“…This etching action eroded cell materials, as a result, cell membrane ruptured and the content effused, and caused cell to die finally [18]. In addition, the chemical reactive species also reacted with the cell materials at the same time.…”
Section: Protein Leakagementioning
confidence: 98%